Central role of lung macrophages in SARS-CoV-2 physiopathology: a cross-model single-cell RNA-seq perspective - Olivier, Thibaut; Blomet, Joël; Desmecht, Daniel (Frontiers in Immunology, 2023)
Cytokine storm is considered as a driving factor of COVID-19 severity. However, the triggering and resolution of this cytokine production as well as the link between this phenomenon and infected cells is still poorly understood. In this study, a cross-species scRNA-seq analysis showed that cytokine producing macrophages together with pneumocytes were found to be the main contributors of viral transcripts in both Syrian hamsters and African green monkeys. Whatever the cell type, viral read bearing cells show an apoptotic phenotype. Comparison of SARS-CoV-2 entry receptor candidates showed that Fc receptors better correlated with infected cells than Ace2, Nrp1 or Axl. Although both species show similar interferon responses, differences in adaptative immunity were highlighted. Lastly, Fc receptor and cytokine upregulation in M1 macrophages was found correlated with a comprehensive interferon response. Based on these results, we propose a model in which lung macrophages play a central role in COVID-19 severity through antibody-dependent enhancement.